Prevalence of Anxiety Symptoms in Medical Students in Inner State of S#xE3;o Paulo, Southeast Brazil (Global Journal of Medical Research, 2021)
Background: Anxiety is a global health concern among medical students. It is associated with difficulty concentrating, insomnia, and a damaged lifestyle. Objectives: To describe anxiety symptoms and to assess the prevalence of anxiety in medical students. Design and Setting: It was conducted a cross-sectional study in a sample of 120 first- to fourth-year medical students in the inner state of S#xE3;o Paulo, Brazil. Methods: An anxiety symptoms formulary was applied to the medical students. There were estimated the prevalence of anxiety and the prevalence ratios according to the variables age, gender, course year, sleep, physical activity, and use of anti-anxiety medication.
Keywords: mental disorders; anxiety disorders; education; medical; undergraduate; epidemiology; prevalence